THE ROLE OF PUBLIC CONTROL IN ENSURING THE EFFICIENCY OF PUBLIC SERVICES - Jomonkulov Bekzod (Web of Journals Publishing, 2025)
The article examines the issue of the dependence of the effectiveness of public services on public oversight. The importance of openness and transparency in the activities of public services in implementing public oversight is substantiated. The importance of arming civil society institutions with knowledge of oversight activities is shown in order to make public oversight effective.
Keywords: Democratic state, civil society, public service, oversight, oversight system, oversight mechanism, public oversight, openness and transparency.